PD-L1 Antibody Pharmacokinetics and Tumor Targeting in Mouse Models for Infectious Diseases - Sandker, Gerwin G. W.; Adema, Gosse; Molkenboer-Kuenen, Janneke; Wierstra, Peter; Bussink, Johan; Heskamp, Sandra; Aarntzen, Erik H. J. G. (Frontiers in Immunology, 2022)
Background: Programmed death-ligand 1 (PD-L1) regulates immune homeostasis by promoting T cell exhaustion. It is involved in chronic infections and tumor progression. Nuclear imaging using radiolabeled anti-PD-L1 antibodies can monitor PD-L1 tissue expression and antibody distribution. However, physiological PD-L1 can cause rapid antibody clearance from blood at imaging doses. Therefore, we hypothesized that inflammatory responses, which can induce PD-L1 expression, affect anti-PD-L1 antibody distribution. Here, we investigated the effects of three different infectious stimuli on the pharmacokinetics and tumor targeting of radiolabeled anti-PD-L1 antibodies in tumor-bearing mice. Materials/Methods: Anti-mouse-PD-L1 and isotype control antibodies were labelled with indium-111 ([111In]In-DTPA-anti-mPD-L1 and [111In]In-DTPA-IgG2a, respectively). We evaluated the effect of inflammatory responses on the pharmacokinetics of [111In]In-DTPA-anti-mPD-L1 in RenCa tumor-bearing BALB/c mice in three conditions; lipopolysaccharide (LPS), local Staphylococcus aureus, and heat-killed Candida albicans. After intravenous injection of 30 or 100 µg [111In]In-DTPA-anti-mPD-L1 or [111In]In-DTPA-IgG2a, blood samples were collected 1, 4, and 24 hours p.i. followed by microSPECT/CT and ex vivo biodistribution analyses. PD-L1 expression, neutrophil, and macrophage infiltration in relevant tissues was evaluated immunohistochemically. Results: In 30 µg [111In]In-DTPA-anti-mPD-L1 injected LPS-challenged tumor-bearing mice, lymphoid organ uptake significantly increased compared with vehicle controls (spleen: 49.9±4.4 %ID/g versus 21.2±6.9 %ID/g, p<0.001), resulting in lower blood levels (3.6±1.6 %ID/g versus 11.5±7.2 %ID/g; p<0.01) and reduced tumor targeting (8.1±4.5 %ID/g versus 25.2±5.2 %ID/g, p<0.001). Local S. aureus infections showed high PD-L1+ neutrophil influx resulting in significantly increased [111In]In-DTPA-anti-mPD-L1 uptake in affected muscles (8.6±2.6 %ID/g versus 1.7±0.8 %ID/g, p<0.001). Hk-C. albicans-challenge did not affect pharmacokinetics. Increasing [111In]In-DTPA-anti-mPD-L1 dose to 100 µg normalized blood clearance and tumor uptake in LPS-challenged mice, although lymphoid organ uptake remained higher. Infectious stimuli did not affect [111In]In-DTPA-IgG2a pharmacokinetics. Conclusions: This study shows that anti-PD-L1 antibody pharmacokinetics and tumor targeting can be significantly altered by severe inflammatory responses, which can be compensated by increasing the tracer dose. This has implications for developing clinical PD-L1 imaging protocols in onco-immunology. We further demonstrate that radiolabeled anti-PD-L1 antibodies can be used to evaluate PD-L1 expression changes in a range of infectious diseases. This supports the exploration of using these techniques to assess hosts’ responses to infectious stimuli